Detection of novel coronaviruses from dusky fruit bat (Penthetor lucasi) in Sarawak, Malaysian Borneo - Sultana Parvin, Habeebur-Rahman; Vaenessa, Noni; Faisal Ali, Anwarali Khan; Tan, Cheng Siang (John Wiley and Sons, 2023)
Background: Sarawak has one of the highest diversity of fruit bats species (family Pteropodidae) in Malaysia, with 19 species described. Most coronavirus (CoV) studies have mainly focused on insectivorous bats, resulting in a lack of information on CoVs present in frugivorous bats. In addition, bat CoV surveillance activities are lacking in Malaysia. Objectives: Our study focuses on determining the presence of bat CoVs in dusky fruit bat (Penthetor lucasi). Methods: Guano samples belonging to P. lucasi were collected from Wind Cave Nature Reserve. The samples were screened for the presence of CoVs using validated heminested consensus RNA-dependent RNA polymerase consensus primers. Results: The bat CoV positivity rate was 38.5% (n = 15/39), with the viruses belonging to two subgenera: Alphacoronavirus (α-CoV) and betacoronavirus (β-CoV). Phylogenetic analysis revealed that CoVs from 14 samples of P. lucasi belong to the genus α-CoV and may represent previously described genetic lineages in insectivorous bats in Wind Cave. However, only one sample of P. lucasi was detected with β-CoV which is closely related to subgenus Nobecovirus, which is commonly seen in frugivorous bats. Conclusions: This study provides the first available data on CoVs circulating in P. lucasi.